Tinjauan Hukum Terhadap Transmisi dan Distribusi Muatan Pornografi Melalui Penyelenggara Sistem Elektronik Lingkup Privat Asing (Twitter) di Indonesia - Rizal Ahmad Fauzi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The development of information and communication technology has changed the direction of interaction to digital in using social media. Twitter is one of the favorite social media to get various information quickly, broadly and directly. However, in current practice, Twitter has become a medium for spreading pornographic content. The purpose of this study is to determine the legal responsibility of Twitter as a Foreign Private Electronic System Operator (PSE) for the distribution and/or transmission of pornographic content carried out by users of the Twitter application based on the provisions of the legislation in Indonesia and to find out legal actions taken by the Government. to Twitter as a PSE to reduce the distribution and/or transmission of pornographic content based on Indonesian laws and regulations. The research method used in writing this thesis is a normative juridical approach with descriptive analytical research specifications. The research was conducted using library research supported by field research. Secondary data collection technique with literature study and supported by primary data in the form of interviews which are then analyzed using qualitative juridical methods. Based on the results of the discussion, it can be concluded that Twitter as a PSE in Indonesia in the form of User Generated Content can be legally held accountable based on the application of the principle of presumption of liability and users who violate the principle of liability based on fault. Legal action taken by the government to limit the spread of pornography on Twitter can be carried out penalized through statutory regulations or non-penalized through preventive and repressive approaches with the presence of a reporting mechanism through dindingkonten.id and virtual police.